Development and implementation of advanced training course for diabetes educators in Argentina - Gagliardino, Juan José (2007)
Purpose. Preliminary report on the development and evaluation of a university-based master's degree program in diabetes education in Latin America. Methods. The program, based on reported international standards, was developed through the Department of Postgraduate Studies of the National University of La Plata, Argentina, with funds provided by the American Association of Diabetes Educators. This highly interactive program combines pedagogical, psychological, and communication-based education specifically related to diabetes. Consequently, its graduates will be prepared to communicate effectively with their patients about their self-care needs and work with them to overcome the day-to-day barriers that prevent them from integrating self-care effectively into their lives. Results. The program was successfully implemented, and 20 students have completed their 1st year, including preparation of a formal master's thesis proposal. During the next year, they will establish and evaluate diabetes education programs in their own communities as part of their master's thesis requirement. Conclusions. We have successfully implemented a master's degree program in diabetes education, based on reported international standards, that provides diabetes knowledge and educational/behavioral principles. Graduates will be able to help ensure patient participation in the control and treatment of their diabetes.